Evaluating the Success Factors of a Tourism Management Information System Using the DeLone and McLean Model: A User Perspective - Hidayat Syah, Rizqi Mulyantara; Oky Dwi Nurhayati; Bayu Surarso (Faculty of Computer Science (FILKOM) Brawijaya University, 2026)
This study evaluates the success factors of a tourism management information system implemented by startup XYZ using the DeLone and McLean Information Systems Success Model. Startups in the tourism industry are becoming more dependent on digital platforms, which prompted this research because there has been little user-centered evaluation of tourism information systems. Involving 75 active users of the system, a quantitative explanatory method was used. A systematic questionnaire with 44 questions was used to gather data. The questions covered topics such as system quality, information quality, service quality, use, user satisfaction, and net benefits. Research methods encompassed creating instruments, collecting data, analyzing it statistically, checking reliability using Cronbach's Alpha, and expert validation with Aiken's V. The instrument demonstrated strong validity and reliability with an overall Aiken's V value of 0.8247. Additionally, all constructs attained Cronbach's Alpha values above 0.70, further supporting these findings. Descriptive statistics, construct correlation, multiple regression, coefficient of determination (R²), and F-test analyses were used to examine the data. All descriptive factors had high mean values, suggesting that users had a good impression of the system. System quality and service quality had a substantial impact on user happiness, according to regression analysis, but information quality and system quality had a substantial impact on system usage. Perceived net benefits were also heavily impacted by system utilization and user satisfaction. The results show that the DeLone and McLean model may be used to evaluate TISs. Making the system more responsive, making the information more accurate, and improving the user support services should be the goals of future enhancements.